Nitrate reductase 15N discrimination in Arabidopsis thaliana, Zea mays, Aspergillus niger, Pichea angusta, and Escherichia coli - Carlisle, Eli; Yarnes, Chris; Toney, Michael D.; Bloom, Arnold J. (Frontiers in Plant Science, 2014)
Stable 15N isotopes have been used to examine movement of nitrogen (N) through various pools of the global N cycle. A central reaction in the cycle involves nitrate (NO3–) reduction to nitrite (NO2–) catalyzed via nitrate reductase (NR). Discrimination against 15N by NR is a major determinant of isotopic differences among N pools. Here, we measured in vitro 15N discrimination by several NRs purified from plants, fungi, and a bacterium to determine the intrinsic 15N discrimination by the enzyme and to evaluate the validity of measurements made using 15N-enriched NO3–. Observed NR isotope discrimination ranged from 22‰ to 32‰ (kinetic isotope effects of 1.022 to 1.032) among the different isozymes at natural abundance 15N (0.37%). As the fractional 15N content of substrate NO3– increased from natural abundance, the product 15N fraction deviated significantly from that expected based on substrate enrichment and 15N discrimination measured at natural abundance. Additionally, isotopic discrimination by denitrifying bacteria used to reduce NO3– and NO2– in some protocols became a greater source of error as 15N enrichment increased. We briefly discuss potential causes of artifactual results with enriched 15N and recommend against the use of highly enriched 15N tracers to study N discrimination in plants or soils.